EVALUACIÓN DE LA CALIDAD DEL AGUA Y FAUNA MACROBENTÓNICA EN EL AFLUENTE Y EFLUENTE PRINCIPAL DE LA LAGUNA SANTO DOMINGO (Perfiles, 2024)
This study evaluates the water quality of the main tributary and effluent of the Santo Domingo Lagoon. The objectives were to analyze the physical-chemical and biological characteristics of the water to determine its influence on water quality, using the ICA-NSF, ICA-Dinius, ABI and IBF indices. For this, samplings were carried out during the months of April and June, evaluating a total of 15 parameters and identifying the benthic macroinvertebrates present in the water bodies. Physicochemical indicators show a slightly higher water quality in April (maximum value 42.2%) compared to June (maximum value 35.5%). Meanwhile, the biological evaluation showed poor water quality at the sampling points with values from 14 to 21 according to the ABI index, while the IBF index indicated excellent quality at the points, suggesting a discrepancy between biological and physicochemical quality. This discrepancy suggests the presence of contaminants that could affect biodiversity in the long term, so it is important to carry out constant and more in-depth monitoring to establish the health of the aquatic ecosystem.